PENGABDIAN MASYARAKAT PENERAPAN TEKNOLOGI TEPAT GUNA ALAT JAHIT KARUNG BERAS SETRA RAMOS - Depy Muhamad Pauzy; Dudu Risana (Politeknik Negeri Sriwijaya, 2021)
The purpose of the Community Service program through the Application of Appropriate Technology is to help producers (Beras Setra Ramos) in developing their business so that they can progress and improve their business, so that they can improve their standard of living and prosper. The way the team took to improve the partners' welfare began with a situation analysis in the field to find out the problems faced by the partners. The method used in the Application of Appropriate Technology is to provide theory and carry out direct activities, namely in the form of practice. In order to support the realization of the methods offered by the service team, the work procedure includes the location survey stage, the preparation / planning stage of the activity, the socialization stage, the activity implementation stage, the evaluation stage, and the report preparation stage. The results of the implementation of this service to partners are: 1) There is an increase in the knowledge of business actors (Beras Setra Ramos) about the importance of quality product attributes ( packaging design ) 2) there is an increase developing soft skill in operating packaging sewing tools 3) there is an increase in the knowledge of product business actors (Setra Ramos Rice) in the application of technology.